National Protocol For Malaria Treatment During Pregnancy - Abdul Hafeez, Abdul Rahman (Gezira Journal of Health Sciences, 2018)
Each year more than 1.2 million women become pregnant in the Sudan, of those 750,000 are in areas with high malaria transmission: intense perennial, high seasonal transmission or in areas of irrigation. Malaria in Africa is estimated to cause 15% of maternal anaemia; about 10,000 maternal deaths / year and 35% of preventable low birth weight. Best practices of malaria control during pregnancy include effective case management of malaria for all women in the reproductive age in malarious areas and using of insecticide treated nets (ITNs) and adopting of intermittent preventive treatment (IPT) with SP. The programme and the partners are targeting 60% coverage with these interventions as Abuja Declaration call for by the end of 2005.